1994
DOI: 10.1002/ccd.1810320303
|View full text |Cite
|
Sign up to set email alerts
|

Perforations after percutaneous coronary interventions: clinical, angiographic, and therapeutic observations

Abstract: Coronary perforation is a rare, but potentially catastrophic, complication of percutaneous coronary intervention. A retrospective review of the Cardiology Quality Assurance Database was performed for all percutaneous coronary interventions (n = 8,932) at William Beaumont Hospital from October 1988 to December 1992. Coronary artery perforation was reported in 35 patients (0.4%), including after percutaneous transluminal coronary angioplasty (PTCA, 11/7,905, 0.14%), transluminal extraction coronary atherectomy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
2
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(139 citation statements)
references
References 16 publications
5
128
2
3
Order By: Relevance
“…11,14 As for new device use, coronary perforation has been reported to occur after 0.25-0.7% of DCA procedures, 11,14,[18][19][20] 0.0-0.7% of rotational atherectomy procedures, 14,21,22 1.3% of extraction atherectomy procedures, and 1.3-3.0% of excimer laser angioplasty procedures. [12][13][14] The present series showed that the incidence of coronary perforation was much higher than of previous reports. The higher rate may be attributable to the prevalence of chronic coronary occlusion interventions at the Institution.…”
Section: Incidence Of Coronary Perforationmentioning
confidence: 99%
See 2 more Smart Citations
“…11,14 As for new device use, coronary perforation has been reported to occur after 0.25-0.7% of DCA procedures, 11,14,[18][19][20] 0.0-0.7% of rotational atherectomy procedures, 14,21,22 1.3% of extraction atherectomy procedures, and 1.3-3.0% of excimer laser angioplasty procedures. [12][13][14] The present series showed that the incidence of coronary perforation was much higher than of previous reports. The higher rate may be attributable to the prevalence of chronic coronary occlusion interventions at the Institution.…”
Section: Incidence Of Coronary Perforationmentioning
confidence: 99%
“…While coronary perforations that are sealed within the catheterization laboratory have a benign prognosis, more severe perforations associated with cardiac tamponade may be associated with high morbidity and mortality. 13 In cases of severe coronary perforation, myocardial infarction rates occur in 16.7-50% 11,12,14 and death results in 9-19%. 11,12,14 In the present series, there were no in-hospital deaths associated with coronary perforation.…”
Section: Early and Late Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Second, it raises the concern, especially with the use of GpIIb/IIIa inhibitor, that in the rare case of a side branch perforation after percutaneous coronary intervention in a patient in whom the bulky covered stent cannot be implanted in the side branch, covering the main branch may be ineffective in preventing tamponade, specifically because of the collateral, which in this scenario, is clearly not "protective." 3,4 Finally, we have a serious concern about the use of a covered stent to treat hypertrophic obstructive cardiomyopathy. There is probably a 20% risk of stent site stenosis, which, in the setting of hypertrophy, might place the patient at high risk for severe and possibly life-threatening ischemia.…”
Section: Covered Stent Septal Ablation For Hypertrophic Obstruction Cmentioning
confidence: 99%
“…Coronary artery perforation (CAP) is a rare but life-threatening complication of percutaneous coronary interventions (PCI) [1,2]. The incidence of CAP has been reported as 0.2-0.8% among all coronary interventions [3].…”
Section: Introductionmentioning
confidence: 99%